Hounds of the basket stitch - Canadeo, Anne, 1955- (Canadeo, Anne, 1955- Black sheep knitting mystery., 2019)
Maggie Messina knows that knitting is not only enjoyable, it also calms both the mind and soul. She<U+2019>s happy to visit two sisters, Holly and Rose Piper, and teach them some simple stitches, while the rest of the Black Sheep knitters tag along. Dana Haeger has known the young women since they were children and is the closest thing to family the Pipers now have. Dana is especially concerned about Rose, who has been easily overwhelmed ever since a car accident many years ago. She is at her best managing the houseful of hounds that she rescues and shelters, while Holly runs the family nursery and remains devoted to Rose<U+2019>s care. The lesson goes well, but the knitters are troubled about the sisters living alone in such a remote corner of Plum Harbor. Their worst fears are realized when Holly is attacked in her greenhouse and the building set ablaze. Rose is found unconscious nearby, her dogs running wild. When she wakes, her memory is blank. Holly is hospitalized and unable to offer even a clue. The Black Sheep suspect a mysterious drifter who had talked his way into a few days of wages, and just as quickly, disappeared. Or was it their estranged half-brother, Toby, full of family grievances and eager to make a claim on the estate? Or, heaven forbid . . . was it Rose? Hovering over all these questions like an ominous shadow is a dark secret from the sisters<U+2019> past. While it seems everything is unraveling, the knitters will need to keep their wits as sharp as their needles to prove Rose<U+2019>s innocence and stop a killer from striking again.